Newspaper coverage of tobacco issues: an analysis of print news in Chinese cities, 2008–2011. Issue 4 (2nd February 2013) - He, Siwei; Shen, Qin; Yin, Xiaoli; Xu, Lianjie; Lan, Xiaoyun
Abstract : Objective: The purpose of this study was to determine to what extent Chinese media coverage of tobacco issues in 17 Chinese cities comprises messaging known to motivate healthy behaviour. Methods: This study involved a content analysis of 4821 articles that contained at least one full paragraph focused on tobacco issues from newspapers published in cities that participated in the Tobacco-Free City—Gates Tobacco Control Project in China between 1 January 2008 and 30 June 2011. Results: The number of tobacco-focused articles increased over the study period. The number of articles varied considerably among different newspapers and cities. Education, prevention and cessation programs (35%) were the most frequent theme. There was also considerable variation in the volume of coverage each month. News articles were the most frequent article type (70%). The majority of the articles (72%) were positive for tobacco control. There were significant differences between party newspapers and local newspapers in prominence, article type, slant and fear appeal. One quarter (n=729) of the articles mentioned the severity of tobacco use, while only 10% of the articles referred to susceptibility to the threat. Conclusions: The coverage of events was predominantly positive toward tobacco control. However, media reports could better support tobacco control efforts if they did a better job at provoking an emotional response to the harms of tobacco use and promoting a sense among smokers that they can succeed in quitting smoking.